A mixed-methods investigation of third and sixth graders’ academic sentence knowledge - Townsend Dianna; Knecht Rachel; Lupo Sarah; Chen Li-Ting; Barrios Vickie Smith (Journal of World Languages, 2023)
This qualitative-dominant mixed methods study aimed to investigate how native English speaking third graders (n = 72) and sixth graders (n = 88) navigate cohesive ties in academic sentences. There are studies on supporting students with academic language at the word and text levels, but less research has been done on readers’ knowledge of the dense and challenging sentences in academic texts. The current study examines both how students navigate cohesion in academic sentences as well as how their knowledge of cohesion relates to their performance on reading comprehension measures. With a multi-case study framework, we analyzed students’ (n = 6) metalinguistic interviews with academic sentences. We then designed Maze tasks for a larger sample (n = 160) to identify patterns in students’ knowledge of cohesion. We also conducted correlational analyses between students’ sentence-level knowledge and performance on measures of reading comprehension. Qualitative findings suggest that students draw on both metalinguistic and epilinguistic knowledge to explain cohesion, and that students value explicit instruction with academic sentences. Quantitative findings show that knowledge of cohesive ties is significantly correlated with performance on reading comprehension measures. Implications and future research for both monolingual and multilingual learners are addressed.